Cell‐Free Protein Synthesis in Bifunctional Hyaluronan Microgels: A Strategy for In Situ Immobilization and Purification of His‐Tagged Proteins. Issue 3 (23rd December 2019) - Heida, Thomas; Köhler, Tony; Kaufmann, Anika; Männel, Max J.; Thiele, Julian
Abstract: In current cell‐free biotechnology, mimicking physicochemical aspects of cellular life while providing efficient protein synthesis, separation, and purification is a crucial step towards truly applicable artificial, yet cell‐like, biosynthesis platforms. To achieve simultaneous synthesis and immobilization of proteins in a tailor‐made environment, we link DNA encoding for histidine‐tagged proteins to microfluidically prepared microgels via strain‐promoted azide‐alkyne cycloaddition and introduce nitrilotriacetic acid moieties that exhibit affinity towards histidine‐tagged proteins upon nickel activation. After swelling the microgels in a prokaryotic protein synthesis machinery, proteins are produced and remain at the site of synthesis despite the membrane‐free, open nature of the gels. The protein‐loaded microgels are then separated from the complex bioreaction mixture and proteins are released by a chemical trigger. Our bifunctional microgels not only contribute to the ongoing design of artificial cells but also allow for directly linking proteins to specific DNA, which can be explored for genotype‐phenotype correlation in DNA mutagenesis. Abstract : Make and do : A bifunctional microgel approach allowing for simultaneously expressing and immobilizing proteins within tailored microgels is introduced.